2021
DOI: 10.1021/acsami.1c14674
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Egg White-Based Carbon Dots as a High-Sensitivity Iron Chelator for the Therapy of Nonalcoholic Fatty Liver Disease by Iron Overload in Zebrafish

Abstract: Iron overload is the direct cause of many ferroptosis diseases, and it is essential to maintain iron homeostasis. In this paper, we report the Fe 3+ chelation and therapy of the iron overload nonalcoholic fatty liver disease (NAFLD) by the fluorescent egg white-based carbon dots (EWCDs) obtained through the microwave-assisted pyrolysis method. As a high-sensitivity sensor, EWCDs show a high correlation between fluorescence emission and the concentration of Fe 3+ (R 2 = 0.993) in low concentration ranges of 0−2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 67 publications
(96 reference statements)
1
40
0
Order By: Relevance
“…Interestingly, iron chelation reversed the levels of these lipid metabolismrelated genes and proteins, implicating that long-term iron overload might promote the synthesis of FFAs, whereas inhibit the consumption of FFAs in the liver, leading to more serious lipid metabolism disorder than NAFLD itself (Figure 7). Several studies also showed that hepatic iron deposition could play a role in the pathogenesis of NAFLD (33)(34)(35). In our study, both iron overload and high fat induced liver steatosis in Possible pathogenesis of NAFLD "multiple hit theory".…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, iron chelation reversed the levels of these lipid metabolismrelated genes and proteins, implicating that long-term iron overload might promote the synthesis of FFAs, whereas inhibit the consumption of FFAs in the liver, leading to more serious lipid metabolism disorder than NAFLD itself (Figure 7). Several studies also showed that hepatic iron deposition could play a role in the pathogenesis of NAFLD (33)(34)(35). In our study, both iron overload and high fat induced liver steatosis in Possible pathogenesis of NAFLD "multiple hit theory".…”
Section: Discussionsupporting
confidence: 63%
“…Current studies on the biology of Nano-ZnO are mainly focused on the antibacterial properties. Studies have shown that Nano-ZnO has antibacterial effects on both foodborne pathogens E. coli and Staphylococcus aureus , among which it is more sensitive to S. aureus [ 28 ]. Ofloxacin is a broad-spectrum antibacterial fluoroquinolone drug.…”
Section: Resultsmentioning
confidence: 99%
“…[62] In 2018, Liu et al have designed probe 22 (Fe@EWCDs) based on an egg white-based carbon dots (EWCDs), which can bind low-concentration Fe 3 + (0-25 μM) with better chelating ability, thus achieving the fluorescence quenching detection of Fe 3 + . [63] Furthermore, they found that probe 22 could inhibit ROS production in the Fenton reaction owing to the chelation of cellular Fe 3 + , thereby inhibiting ER stress and hepatocyte apoptosis, and regulating adipocyte metabolism. In addition, probe 22 was successfully applied to alleviate iron overload-induced NAFLD in zebrafish by regulating the NF-kB signaling pathway downstream of the Nrf2 signaling pathway.…”
Section: Ions Probes With Fluorescence Imagingmentioning
confidence: 99%